Failing to Plan Is Planning to Fail - The Importance of Planning Phase in Logistics Outsourcing, 2 Cases from Bulgaria - Fileva, Petya (Research Papers, 2020)
The research identifies problems during the initiation and planning stages of logistics outsourcing projects, and their impact based on real business situation case studies from the sector in Bulgaria. The study highlights possible problems and risks during the early stages and planning when it's still possible to mitigate them and increase the chances for project success, the methodology is based on case study analysis comparing two real outsourcing projects from Bulgaria.
Keywords: Logistics outsourcing; Logistics service provider; Case study